2012
DOI: 10.1093/chemse/bjs061
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Carbonation and Temperature on Water Swallowing Performance: A Swallowing Reaction-Time Study

Abstract: Various therapeutic approaches for dysphagia management are based on modifications of bolus properties to change swallowing biomechanics and increase swallowing safety. Limited evidence exists for the effects of carbonation and bolus temperature on swallowing behavior. Here, we investigated the effects of carbonation and temperature on swallowing behavior using a novel automated and complex swallowing reaction time task via pressure signal recordings in the hypopharynx. Healthy participants (n = 39, 27.7±5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 40 publications
3
57
0
Order By: Relevance
“…20,22 To control for temperature, the still water (SW) was also kept at 6°C to match the temperature of the CW. The liquid solutions were then infused into the subject's mouth with single use plastic syringes and manual injection of 5 mL boluses down a small plastic single-use tube.…”
Section: Carbonated and Still Water Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,22 To control for temperature, the still water (SW) was also kept at 6°C to match the temperature of the CW. The liquid solutions were then infused into the subject's mouth with single use plastic syringes and manual injection of 5 mL boluses down a small plastic single-use tube.…”
Section: Carbonated and Still Water Solutionsmentioning
confidence: 99%
“…The conversion of CO 2 to carbonic acid in carbonated water (CW) leads to the activation of oropharyngeal nociceptors 14,15 , which excites neurons involved in signaling somatosensory inputs. 14,16,17 Several existing studies have reported the positive effect of carbonation not only on swallowing behavior during swallowing carbonated bolus [18][19][20] but also on subsequent swallowing movement. 21 Recently, it has been revealed that swallowing a carbonated solution provokes increases in (pharyngeal) cortical excitability, 22 which also implies that it can induce neuroplasticity in sensorimotor cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout a feeding session, sucking is an ongoing rhythmic behavior, and suckswallow cycles occur every one to three suck cycles early during a feeding session and are less frequent toward the end. Although we know some of the sensory mechanisms that elicit the swallow in adults, including bolus volume, temperature, taste, and carbonation (Butler et al 2011;Michou et al 2012;Yamamura et al 2010), it is unknown how specific sensory information gathered during the oral transport process impacts the onset of the reflexive pharyngeal swallow in infants.…”
mentioning
confidence: 99%
“…The majority of research suggests minimal effects of temperature on pharyngeal peristalsis [21], duration of true vocal fold closure [22], and elicitation of a pharyngeal swallow [23]. A recent study identified changes in swallowing reaction times (time from cue to swallow until onset of the pharyngeal swallow) with both cold and carbonated liquids [24]. No significant swallowing effects were identified with a cold bolus in patients with dysphagia following stroke [25].…”
Section: Temperaturementioning
confidence: 99%
“…The use of carbonation was designed to decrease post swallow residue and reduce airway invasion occurring before onset of the pharyngeal swallow [17]. Findings are variable concerning the effects of carbonation on swallowing in healthy adults with some studies showing improvement on various outcomes [24,26], and other identifying no changes [27]. Studies in the neurogenic population are more uniform concerning positive effects of carbonated beverages on swallowing with reduced post swallow residue [28,29], reduced airway invasion [28,30], and decreased pharyngeal transit time [28] identified.…”
Section: Carbonationmentioning
confidence: 99%